A Reconstituted Capsid-Nucleus Platform Uncovers Distinct Roles of UL25 and UL36 in Herpesvirus Capsid Docking - Tsimtsirakis, Efthymios; Villanueva-Valencia, Jose Ramon ; 0000-0003-4733-0368; Huffman, Jamie B.; Homa, Fred; Evilevitch, Alex ; 0000-0002-0245-9574 (Journal of Molecular Biology, 2025)
Herpes simplex virus type 1 (HSV-1) delivers its genome into the host nucleus via docking of the viral capsid at the nuclear pore complex (NPC), a process mediated by the capsid vertex-specific complex (CVSC), composed of UL17, UL25, and UL36. While prior in vivo studies have implicated UL25 and UL36 in NPC interactions, their interpretation is complicated by indirect effects from viral trafficking, host responses, and capsid stability defects resulting from CVSC protein deletions. To isolate the nuclear docking step, we employed a reconstituted in vitro system using purified fluorescent HSV-1 capsids (wild-type, ΔUL25, ΔUL36) and isolated mammalian nuclei. Quantitative confocal imaging analysis revealed a marked reduction in docking upon UL36 deletion, while UL25 deletion similarly impaired binding, likely due to loss of UL36 incorporation and compromised capsid integrity. These findings suggest UL36 is a key mediator of NPC engagement, with UL25 supporting CVSC assembly and stability. This reductionist platform enables precise dissection of herpesvirus nuclear entry mechanisms.